Poetics of visibility in the contemporary Arab American novel - Naous, Mazen (The Ohio State University Press, 2020)
""Redefines dominant perceptions of Arab Americans via an aesthetic analysis of Arab American novels, such as Diana Abu-Jaber's Arabian Jazz and Crescent, Rabih Alameddine's Koolaids: The Art of War, Laila Halaby's Once in a Promised Land, and Mohja Kahf's The Girl in the Tangerine Scarf, thereby launching transcultural possibilities by initiating visibility through poetics"--Provided by publisher"--